2022
DOI: 10.5650/jos.ess21360
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a Model Biofilm by Sophorolipid Solutions: A QCM-D Study

Abstract: used in many applications such as cosmetics, agriculture, and the food industry owing to their biodegradability and low toxicity compared to chemical surfactants 8−10) . In addition to these benefits, biosurfactants have properties that are suitable for cosmetic applications, such as compatibility with human skin and skin surface moisturizing 10) .Furthermore, consumers pay more attention to natural products when considering environmental sustainability 11) . Therefore, biosurfactants have scope to be further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, the overall reaction was exothermic, which might be the result of demicellization of sophorolipids or the presence of other exothermic interactions, such as hydrogen bonding. Our previous study suggested that sophorolipids interfere with the hydration bonds between the β-glucan molecules during β-glucan film removal, as evaluated using a quartz crystal microbalance with dissipation monitoring measurements 22) . Hence, hydrogen bonding may also be involved in this interaction.…”
Section: Itc Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the overall reaction was exothermic, which might be the result of demicellization of sophorolipids or the presence of other exothermic interactions, such as hydrogen bonding. Our previous study suggested that sophorolipids interfere with the hydration bonds between the β-glucan molecules during β-glucan film removal, as evaluated using a quartz crystal microbalance with dissipation monitoring measurements 22) . Hence, hydrogen bonding may also be involved in this interaction.…”
Section: Itc Measurementsmentioning
confidence: 99%
“…Sophorolipids is a type of biosurfactants, which have been reported to be effective in the disruption 17−20) and removal 21) of biofilms. In our previous study on polysaccharides in EPS, which was focused on their contributions to the adhesion and mechanical stability of biofilms, we found that sophorolipids contributed on the removal of model EPS generated by a β-glucan 22) using quartz crystal microbalance with dissipation monitoring measurements. β-glucan forms triple helix in aqueous solution 23) .…”
mentioning
confidence: 99%
“…Recently, Kaga et al 37 studied the removal of a β-glucan film by surfactants, showing that QCM-D allows to assess the BF removal in real time, by monitoring the viscoelasticity of the β-glucan films. However, since experiments were performed under flow in a liquid environment, the data treatment becomes more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by simultaneously measuring energy dissipation, it provides valuable information about the viscoelasticity of the adsorbed layer. QCM-D can also be used to monitor the cleaning dynamics, as long as the shear wave is still present in the adsorbed film, and this technique has been applied in several recent studies. , However, despite its compatibility with QCM-D, the removal dynamics in the electronics industry, which demands high-precision cleanliness, is still unclear. This emphasizes the potential of QCM-D as an analysis platform for evaluating new cleaning methods using interfacial technology.…”
Section: Introductionmentioning
confidence: 99%